PEMBUATAN VIDEO SEBAGAI MEDIA IKLAN MENGGUNAKAN APLIKASI MAGIX SONY VEGAS PRO 18 PADA BAKSO BAKAR KANG HER DI MALANG - Nur Taufiq Ardiansyah Ahmad; Tri Istining Wardani (ADISAM PUBLISHER, 2024)
The development of technology is proof that the world of science and technology is always growing and innovating rapidly. The amount of information technology is also a means of delivering advertising messages for a product through advertising videos. The purpose of this research is to make videos as advertising media using the Magix Sony Vegas Pro 18 application can make customers interested in products at Bakso Bakar Kang Her. The type of research used is Action Research with research procedures consisting of planning, action, observing, and reflecting. The effectiveness of the video in this study was analyzed based on the distribution of questionnaires using the EPIC Model (Empathy, Persuasion, Impact, Communication) method. The questionnaire was distributed to 1 business owner, 2 marketing experts, 2 computer experts and 5 potential customers. Based on the results of the score calculation by distributing questionnaires to several respondents in this study and each dimension that has been calculated using the EPIC Model gets a score of 4.8. The EPIC score results show that the advertising videos made in this study are very effective. The conclusion of this study shows that the advertising videos made are very effective to be published on Bakso Bakar Kang Her's Instagram. The advertising video can be used as an advertising medium to potential consumers so that they can be interested in the product